Low Frequency Noise Reduction with Active Noise Control in Laboratory Settings - Junsupasen, Suparoek; Pongyart, Witthawas; Jongprasithporn, Manutchanok; Yodpijit, Nantakrit (Applied Science and Engineering Progress, 2018)
Noise problem becomes a major concern for public health throughout the world. This research is conducted to investigate how to reduce low-frequency noise in laboratory settings using Active Noise Control (ANC) technique. Experiments are performed under two conditions: 1) in a close room (6.7 m wide, 11 m long, and 2.87 m high), and 2) in an open field (8.2 m wide and 18 m long). Low-frequency noise at 200 Hz is generated by the 1,000 W speaker (as noise source), and the 1,200 W speaker is used as noise cancelling speaker. Error microphone and spectrum analyzer are installed for measuring noises. Findings indicate that noise reductions of 14.38 dB and 10.73 dB can be made in a close room and in an open field, respectively. Applications and limitations for this research are also discussed.